Chapter La lingua italiana come strumento di parità di genere nelle Università - ROBUSTELLI, Cecilia (Proceedings e report, 2023)
The paper examines the studies on the relationship between language, sex and gender in Italian academia; the search for non-sexist linguistic strategies for the representation of women and men; the related support of international political action; the recent EU Equality Strategies; and the action of the CRUI Commission on Gender Issues.